Comprehension of drug toxicity: software and databases - Toropov, Andrey A; Toropova, Alla P; Raska, Ivan; Leszczynska, Danuta; Leszczynski, Jerzy (Computers in biology and medicine, 2014)
Quantitative structure-property/activity relationships (QSPRs/QSARs) are a tool (in silico) to rapidly predict various endpoints in general, and drug toxicity in particular. However, this dynamic evolution of experimental data (expansion of existing experimental data on drugs toxicity) leads to the problem of critical estimation of the data. The carcinogenicity, mutagenicity, liver effects and cardiac toxicity should be evaluated as the most important aspects of the drug toxicity. The toxicity is a multidimensional phenomenon. It is apparent that the main reasons for the increase in applications of in silico prediction of toxicity include the following: (i) the need to reduce animal testing; (ii) computational models provide reliable toxicity prediction; (iii) development of legislation that is related to use of new substances; (iv) filling data gaps; (v) reduction of cost and time; (vi) designing of new compounds; (vii) advancement of understanding of biology and chemistry. This mini-review provides analysis of existing databases and software which are necessary for use of robust computational assessments and robust prediction of potential drug toxicities by means of in silico methods.
Keywords: kvantitativní vztahy mezi strukturou a aktivitou; testy toxicity; Computer Simulation; výpočetní biologie; počítačová simulace; Drug toxicity; databáze faktografické; Quantitative Structure-Activity Relationship; In silico toxicology; zvířata; Humans; Software; Toxicity Tests; In silico methods; software; nežádoucí účinky léčiv; Computational Biology; Drug-Related Side Effects and Adverse Reactions; Computational toxicology; Databases, Factual; QSAR; lidé; Animals